Hybrid Procedures. Opening Doors for Surgeon and Cardiologist Close Collaboration - Gil-Jaurena, Juan-Miguel; Zunzunegui, José-Luis; Pérez-Caballero, Ramón; Pita, Ana; Pardo, Carlos; Calle, Corazón; Murgoitio, Uxue; Ballesteros, Fernando; Rodríguez, Alejandro; Medrano, Constancio (Frontiers in Pediatrics, 2021)
Background. Surgeon and cardiologist on their own cannot cope with patients needs, occasionally. Hypoplastic left heart syndrome witnessed the collaboration between them for a palliative, hybrid procedure. As a strategy, hybrid approach has been applied in several, unforeseeable settings. Our initial experience is presented, pointing at indications, shortcomings and mid-term results. Methods. Seventy-one patients were scheduled for a hybrid procedure along eight years. This was defined as: close collaboration between surgeon and cardiologist working together in the same room, either cath-lab (27 patients) or theatre (44 patients) Results. Six groups were arbitrarily defined. A: vascular cut-down in the cath-lab (27 neonates); B: bilateral banding (plus ductal stent) in hypoplastic left heart syndrome or alike (15 children); C: perventricular closure of muscular ventricular septal defect (10 cases); D: Balloon/stenting of pulmonary branches along with major surgical procedure (12 kids); E: surgical implantation of Melody valve (6 patients) and others (F, 1 case). Two complications were recorded: left ventricular free wall puncture and previous conduit tearing. Both drawbacks were successfully sort out under cardiopulmonary by-pass. Conclusion. Surgeon and cardiologist partnership can succeed where their isolated endeavors are not enough. Hybrid procedures keep on spreading, overcoming initial expectations. As a bridge to biventricular repair or transplant, bilateral banding plus ductal stent sounds interesting. Novel indications can be classified into different groups. Hybrid procedures are not complication-free.